The Comprehensive Role of Physical Exercise in Enhancing Mental Health: An Academic Review of Current Evidence and Implications for Treatment Strategies - ALMutlaqah, Mubarak Nasser; Al-Mutairi, Jazaa Mohsen; Ali, Waleed Khaled; ALMUTAYRI, Amal mubark hazzaa; Al-Dhafiri, Muhammad Kamel Mayouf; Thubab, Abdulaziz Hassan Ahmed; Qaysi, Abdulaziz Omar Hassan; Alrasheedi, Mariam Mohammed; alharbi, khulood atiq; Taleb , Khalid Ali M; ALDHAFEEEI, HADEEL KHALID AJMI; Alharbi , Nojod Atiq; et al. (Journal of Ecohumanism, 2024)
Background: The relationship between physical exercise and mental health has garnered increasing attention due to the rising prevalence of mental health disorders globally. Exercise is recognized not only for its physical health benefits but also for its potential role in improving mental well-being. This review synthesizes current evidence on the impact of exercise on various aspects of mental health, including depression, anxiety, and other psychological conditions. Methods: A systematic literature search was conducted across multiple databases, focusing on studies that explored the physiological and psychological mechanisms by which exercise influences mental health outcomes. Keywords such as "exercise," "physical activity," "mental health," "depression," and "anxiety" were employed to identify relevant research articles. Results: The review identified substantial evidence indicating that regular physical activity is associated with improvements in mood, reductions in anxiety, and enhanced overall mental health. Meta-analyses revealed that exercise can significantly alleviate symptoms of depression and anxiety, often comparable to traditional pharmacological treatments. Furthermore, specific modalities, such as yoga, demonstrated unique benefits for mental health, particularly in individuals with conditions like schizophrenia and substance use disorders. Conclusion: The findings support the integration of exercise as a foundational component in the treatment and management of mental health disorders. Given its accessibility and low cost, exercise can serve as a practical adjunct to conventional therapeutic approaches. Future research should focus on establishing standardized exercise protocols tailored to individual needs, particularly in diverse contexts, including developing countries